2018
DOI: 10.3389/fendo.2018.00694
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Fat and Hematopoiesis

Abstract: Bone marrow fat cells comprise the largest population of cells in the bone marrow cavity, a characteristic that has attracted the attention of scholars from different disciplines. The perception that bone marrow adipocytes are “inert space fillers” has been broken, and currently, bone marrow fat is unanimously considered to be the third largest fat depot, after subcutaneous fat and visceral fat. Bone marrow fat (BMF) acts as a metabolically active organ and plays an active role in energy storage, endocrine fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 107 publications
(130 reference statements)
0
56
0
Order By: Relevance
“…37 Adiponectin has been shown to enhance the proliferation of hematopoietic stem cells and maintain their undifferentiated state. 36 The results of our study showed that the leptin-to-adiponectin ratio was significantly related to the RDW values. This relationship was relevant after adjusting for age and sex.…”
Section: Methods Subjectsmentioning
confidence: 51%
See 1 more Smart Citation
“…37 Adiponectin has been shown to enhance the proliferation of hematopoietic stem cells and maintain their undifferentiated state. 36 The results of our study showed that the leptin-to-adiponectin ratio was significantly related to the RDW values. This relationship was relevant after adjusting for age and sex.…”
Section: Methods Subjectsmentioning
confidence: 51%
“…16,20 In this context, it is very interesting that adipocytes account for about 50% of bone marrow cells and occupy 70% of adult bone marrow volume. 15,36 Leptin is a 16-kDa peptide hormone, produced predominantly by mature adipocytes, which is involved in regulating body energy balance and body fat. 16 In adults, serum leptin levels are correlated with the percentage of body fat.…”
Section: Adipokine Imbalance and Anisocytosismentioning
confidence: 99%
“…Chondrocytes originate from mesenchymal stem cells [ 71 , 72 ]. Bone-marrow-derived MSCs (BM-MSCs) have much promise in aiding articular cartilage repair due to their proximity to the joint, high differentiation capability, and ability to secrete different growth, anti-inflammatory, and immunomodulatory factors [ 73 , 74 , 75 , 76 , 77 ]. They could affect a clinically relevant improvement in joint pain and function.…”
Section: Mesenchymal Stem Cells and Tissue Regenerationmentioning
confidence: 99%
“…They directly induce MM cell expansion through the huge amount of cytokines that they produce [6] and via the secreted exosomes [11]. They can dialogue directly with MM cells through close contact [7,12] and membrane exchange, inducing chemoresistance acquisition [13]. They also play a role in the recruitment of other microenvironment cells involved in tumor cell growth, chemoresistance acquisition, and depletion of the immune responses [14][15][16] Our own studies and that of other authors have shown that MSC from patients with newly diagnosed MM are abnormal [11,17], as they acquire pro-tumor potentialities.…”
Section: Introductionmentioning
confidence: 99%